Is the perceived neighborhood built environment associated with domain-specific physical activity in Latin American adults? An eight-country observational study - Gerson Ferrari; André Oliveira Werneck; Danilo Rodrigues da Silva; Irina Kovalskys; Georgina Gómez; Attilio Rigotti; Lilia Yadira Cortés Sanabria; Martha Yépez García; Rossina G. Pareja; Marianella Herrera-Cuenca; Ioná Zalcman Zimberg; Viviana Guajardo; et al. (BMC, 2020)
Abstract Background Characteristics of the neighborhood built environment are associated with physical activity (PA). However, few studies with representative samples have examined environmental correlates of domain-specific PA in Latin America. We examined the associations of the perceived neighborhood built environment with domain-specific PA in a large sample of adults from eight Latin American countries. Methods This study examined data from 8185 adults (aged 18-65 years) from eight Latin American countries. The Neighbourhood Environment Walkability Survey - Abbreviated (NEWS-A) scale was used to assess perceptions of land use mix-diversity, land use mix-access, street connectivity, walking/cycling facilities, aesthetics, safety from traffic, and safety from crime. Perceived proximity from home to public open spaces (metropolitan parks, playgrounds, public squares) and to shopping centers was also measured. Transport-related and leisure-time PA were assessed using the long form of the International Physical Activity Questionnaire. Both logistic and linear regression models were estimated on pooled data. Results Perceptions of higher land use mix-access (OR: 1.40; 95% CI: 1.22,1.61), the existence of many alternative routes in the neighbourhood (1.12; 1.04,1.20), slow speed of traffic (1.19; 1.03,1.35) and few drivers exceeding the speed limits (1.09; 1.03,1.15) were associated with greater odds of reporting at least 10 min/week of transport-related PA. Perceptions of higher levels of land use mix-diversity, better aesthetics and greater safety from crime, the presence of crosswalks and pedestrian signals, and greater proximity of shopping centers were associated with more min/week of transport-related PA. Perceptions of higher land use mix-diversity (1.12; 1.05,1.20), higher land use mix-access (1.27; 1.13,1.43), more walking/cycling facilities (1.18; 1.09,1.28), and better aesthetics (1.10; 1.02,1.18) were associated with greater odds of engaging in at least 10 min/week of leisure-time PA versus none. Perceptions of higher land use mix-diversity were associated with more min/week of leisure PA. Conclusions Different perceived neighborhood built environment characteristics were associated with domain-specific PA among adults from Latin America countries. Interventions designed to modify perceptions of the neighbourhood built environment might influence initiation or maintenance of domain-specific PA. Trial registration ClinicalTrials. Gov NCT02226627 . Retrospectively registered on August 27, 2014.